"I My Self": Queen Elizabeth I's Oration at Tilbury Camp - Green, Janet M. (The sixteenth century journal, 1997)
Queen Elizabeth I made one of her most famous speeches on August 9, 1588, at Tilbury Camp. Its authenticity has been doubted occasionally, but substantial evidence indicates that it is genuine. Its internal rhetorical characteristics link this oration strongly to Elizabeth's others. Also, considerable contemporary evidence exists that she delivered a speech at Tilbury whose phrases, often remarked, were like those of the speech we have. Finally, one of the two surviving texts-BM Harleian MS 6798, article 18-is in the handwriting of another, namely of Dr. Leonel Sharpe, author of a 1623 letter first published in the Cabala of 1654, in which Sharpe (almost certainly an eyewitness at Tilbury) gives the now familiar text. Though the Harleian MS is in a few places literarily inferior to the Cabala text, it is nevertheless an important link to that text and shows with much more certainty that both are genuine.